A sinalização do gerenciamento de resultados por meio da responsabilidade social corporativa no Brasil - Silva Júnior, Francisco José da (2020)
This research aimed to study the relationship between Corporate Social Responsibility and the Earnings Management level practiced by managers, from the perspective of the Signaling Theory. It is known that companies started to show voluntary information as a way to reduce the existing asymmetry with stakeholders, ensuring greater appreciation. In this way, managers can take advantage to practice discretionary attitudes, biasing the real feeling of voluntary disclosure. The literature points to an ambiguous relationship between such variables, with managers being able to use CSR ethically, reducing the level of EM and contributing to better information quality; or an opportunistic stance, shifting the investors’ focus to manipulative attitudes about profits. Thus, we sought to analyze this relationship, taking as a sample the non-financial listed companies in Brazil, Bolsa Balcão (B3), nonfinancial, from the post-adoption period of IFRS, from 2010 to 2018. To define the Earnings Management level, the Pae model (2005) was used, with the residual regression module (GRit) being the dependent variable, estimated by GMM (System Generalized Method of Moments). As for the proxy for Corporate Social Responsibility disclosure, it was estimated through content analysis of the Sustainability Reports, Reference Forms and Explanatory Notes of the companies, capturing the presence of 43 economic, environmental and social indicators, based on Callado (2010 ) and Murcia and Wuerges (2011). As a control, return of assets (ROAit), leverage (ENDit), corporate governance (GOVit), market-to-book (MTBit) and sector (∑SETORit) made up the models. By results, it was identified that the disclosure of CSR associated with the environmental’s information would be positively associated with higher levels of EM. Thus, the presence of more environmental’s information may signal possible manipulation of profits, served as a warning to stakeholders.